2003
DOI: 10.1021/ja0379215
|View full text |Cite
|
Sign up to set email alerts
|

Probing Photoelectrochemical Processes in Au−CdS Nanoparticle Arrays by Surface Plasmon Resonance:  Application for the Detection of Acetylcholine Esterase Inhibitors

Abstract: The photoelectrochemical charging of Au-nanoparticles (NP) in a Au-nanoparticle/CdS-nanoparticle array assembled on a Au-coated glass surface is followed by means of surface plasmon resonance (SPR) spectroscopy upon continuous irradiation of the sample. The charging of the Au-NPs results in the enhanced coupling between the localized surface plasmon of the Au-NP and the surface plasmon of the bulk surface, leading to a shift in the plasmon angle. The charging effect of the Au-NPs is supported by concomitant el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
124
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 49 publications
1
124
0
1
Order By: Relevance
“…They measured the absorption spectra of the GNP monolayers in which GNPs were immobilized upon a glass slide by a functional organic coupling agent and found an optical response to polymers of different refractive indexes that were spin-cast on the immobilized GNPs [26]. Subsequently, a series of papers from different labs have presented this chip-based format optical biosensor, in which GNPs are immobilized on an optically transparent substrate [22,23,25,[45][46][47][48][49]. For instance, Matsui et al demonstrated a SPR sensor chip for detection of small molecules like dopamine [47].…”
Section: Gnp-based Optical Biosensorsmentioning
confidence: 99%
“…They measured the absorption spectra of the GNP monolayers in which GNPs were immobilized upon a glass slide by a functional organic coupling agent and found an optical response to polymers of different refractive indexes that were spin-cast on the immobilized GNPs [26]. Subsequently, a series of papers from different labs have presented this chip-based format optical biosensor, in which GNPs are immobilized on an optically transparent substrate [22,23,25,[45][46][47][48][49]. For instance, Matsui et al demonstrated a SPR sensor chip for detection of small molecules like dopamine [47].…”
Section: Gnp-based Optical Biosensorsmentioning
confidence: 99%
“…Hierarchical self-assembly of nanoparticles into a 2-D or 3-D superlattice facilitates manipulation of the structures with enhanced and tunable quantum confinement effects which opens up the possibilities of developing new classes of nanomaterials and devices with potential applications in light emitting diodes [2], Nano Res (2009) 2: 220 234 solar cells [3], molecular electronic architectures [4], high-density data storage [5], catalysis [6], biochemical sensors [7,8], biocompatible materials [9], and so on. The tremendous interest in particle superlattices is also driven by their already established applications in various fields resulting from the collective properties of the building blocks, which help us to understand electronic effects such as the metal-insulator transition and changes in magnetic and optical properties [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…C rystalline aggregates composed of one or more types of metallic and/or semiconductor nanoparticles (NPs) are of great interest for the development of new materials with potential applications in areas such as optoelectronics (1), high-density data storage (2), catalysis (3), and biological sensing (4). To date, methods for the crystallization of two-dimensional (2D) and 3D NP superlattices have relied on the differences in the sizes of component particles and on attractive van der Waals or hard-sphere interactions between them.…”
mentioning
confidence: 99%
“…Measurements on molecular hydrogen and deuterium agreed well with calculations of ultrafast nuclear dynamics in the H 2 þ molecule, confirming the validity of the method. We then measured harmonic spectra from CH 4 and CD 4 to demonstrate a fewfemtosecond time scale for the onset of proton rearrangement in methane upon ionization.…”
mentioning
confidence: 99%
See 1 more Smart Citation